Missing and Possible Link between Neuroendocrine Factors, Neuropsychiatric Disorders, and Microglia - Kato, Takahiro A.; Hayakawa, Kohei; Monji, Akira; Kanba, Shigenobu (Frontiers in Integrative Neuroscience, 2013)
Endocrine systems have long been suggested to be on of the important factors in neuropsychiatric disorders, while the underlying mechanisms have not been well understood. Traditionally, neuropsychiatric disorders have been mainly considered the consequence of abnormal conditions in neural circuitry. Beyond the neuronal doctrine, microglia, one of the glial cells with inflammatory/immunological functions in the CNS, have recently been suggested to play important roles in neuropsychiatric disorders. However, the crosstalk between neuroendocrine factors, neuropsychiatric disorders and microglia has been unsolved. Therefore, we herein introduce and discuss a missing and possible link between these three factors; especially highlighting the following hormones; (1) Hypothalamic-Pituitary-Adrenal (HPA) axis-related hormones such as corticotropin-releasing hormone (CRH) and glucocorticoids, (2) sex-related hormones such as estrogen and progesterone, and (3) oxytocin. A growing body of evidence has suggested that these hormones have a direct effect on microglia. We hypothesize that hormone-induced microglial activation and the following microglia-derived mediators may lead to maladaptive neuronal networks including synaptic dysfunctions, causing neuropsychiatric disorders. Future investigations to clarify the correlation between neuroendocrine factors and microglia may contribute to a novel understanding of the pathophysiology of neuropsychiatric disorders.